Порівняльний аналіз сучасних web-фреймворків - Авідзба, В. Ю. (ХНУРЕ, 2023)
The work is devoted to researching the comparison of two contemporary front-end frameworks such as React.js and Vue.js. The two frameworks are considered as those who develop most rapidly and also considered to be the most popular ones. They are compared in different aspects: from general information, paradigms, project building approach to technical features provided by both the frameworks. The theses also research and propose the answer to the question of which framework to choose depending on the project that is wanted to be built